1997
DOI: 10.1063/1.365936
|View full text |Cite
|
Sign up to set email alerts
|

Fast, high-resolution atomic force microscopy using a quartz tuning fork as actuator and sensor

Abstract: We report a new method of achieving tip-sample distance regulation in an atomic force microscope ͑AFM͒. A piezoelectric quartz tuning fork serves as both actuator and sensor of tip-sample interactions, allowing tip-sample distance regulation without the use of a diode laser or dither piezo. Such a tuning fork has a high spring constant so a dither amplitude of only 0.1 nm may be used to perform AFM measurements. Tuning-fork feedback is shown to operate at a noise level as low as that of a cantilever-based AFM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
109
0
10

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 11 publications
1
109
0
10
Order By: Relevance
“…Güethner et al 7 have used tuning forks as a force sensor in acoustic near field microscopy and Karrai et al 8 have used a tuning fork to control the distance between the optical fiber and the surface in a scanning near-field-optical microscope. Recently, Edwards et al 9 have demonstrated a faster mode using a phase-locked-loop detector.…”
Section: ͓S0003-6951͑98͒00152-1͔mentioning
confidence: 99%
See 1 more Smart Citation
“…Güethner et al 7 have used tuning forks as a force sensor in acoustic near field microscopy and Karrai et al 8 have used a tuning fork to control the distance between the optical fiber and the surface in a scanning near-field-optical microscope. Recently, Edwards et al 9 have demonstrated a faster mode using a phase-locked-loop detector.…”
Section: ͓S0003-6951͑98͒00152-1͔mentioning
confidence: 99%
“…16 The acquisition speed was 12 lines per second ͑lps͒ and the width of the image is 9.6 m, thus the scanning speed is 230 m/ s-100 times faster than in previous implementations. 9 Figure 5 presents an image of a calibration grating. Here, the tip of the QPS is a small crystal of sapphire ͑approx.…”
Section: ͓S0003-6951͑98͒00152-1͔mentioning
confidence: 99%
“…Tuning forks have been used in scanning probe microscopes before. [9][10][11][12][13][14][15][16][17] However, atomic resolution has not been reported so far.…”
mentioning
confidence: 99%
“…Scanning is performed with an electrochemically etched metallic tip attached to the end face of one prong of a piezoelectric quartz tuning fork [8,9,10,11,12].…”
mentioning
confidence: 99%